In situ synthesis of ligand reduced/capped silver nanoparticles and the effect of temperature and ligand structure on the size of silver nanoparticles - Kasture, M. B.; Patel, P.; Prabhune, Asmita; Ramana, C. V.; Kulkarni, A. A.; Bhagavatula L. V. Prasad (Journal of Chemical Sciences, 2008)
We report in situ synthesis of silver nanoparticles using biosurfactants called sophorolipids as reducing and capping agents. We further study the effect of temperature and the structure of sophorolipid on the size of silver nanoparticles obtained. The silver nanoparticles were characterized by UV-visible, transmission electron microscope (TEM) and light scattering (DLS) analysis techniques.
International Conference on Molecules and Materials - New Directions, Bangalore, INDIA, DEC 04, 2008
Keywords: dynamic light scattering; Nucleation and growth; silver nanoparticles; Sophorolipid

Biomimetic synthesis of selenium nanoparticles using cell-free extract of microbacterium sp ARB05 - Prasad, K. S.; Vyas, P.; Prajapati, V.; Patel, P.; Selvaraj, K. (Micro & Nano Letters, 2012)
This Letter is a novel approach to synthesise a bio-functionalised selenium nanoparticles using cell-free extract of selenium-resistant bacterial isolate. Phylogenetic analysis of isolate suggested its close similarity with Microbacterium luteolum (Y17235.1) and Microbacterium oxydans str. TPL09 (EU373379.1) while it was distantly related to Microbacterium dextranolyticum (Y17230.1). Selenium colloidal solution exhibited an absorption maximum at 300 nm and gave emission maximum at 590 nm. Transmission electron microscopy followed by selected area electron diffraction pattern analysis indicated the formation of spherical, polydispersed, crystalline, Se nanoparticles of diameter ranging from similar to 30 to 150 nm. X-ray diffraction results showed 111, 200 and 220 planes of face-centred cubic selenium. Energy dispersive analysis of X-rays confirmed the presence of selenium in nanosphere. Selenium nanoparticles synthesised in this manner can be studied for chemo-prevention as well as its fluorescent property can be utilised for molecular diagnostics in cancer research.

Metabolic engineering: achieving new insights to ameliorate metabolic profiles in Withania somnifera - Patel, N.; Patel, P.; Khan, B. M. (Medicinal plants - recent advances in research and development, 2016)
Withania somnifera, commonly known as Indian ginseng, has been used for centuries in Ayurvedic system of medicine for its antitumor, antioxidant, antiaging, antiserotogenic, and antistress activities. The various medicinal properties of the plant are accredited to the steroidal lactones (withanolides) present in the plant. Withanolides are synthesized by diverting the metabolite flux away from the isoprenoid pathway by the reductive condensation of farnesyl diphosphate to squalene through the activity of the enzyme squalene synthase. This enzyme squalene synthase is a major branch point involved in the regulation of withanolides. Owing to low concentrations of these bioactive compounds in plant, large biomass is utilized for the preparation of medicinal formulations in pharmaceutical industries to fulfill the growing commercial demand. To protect Withania spp. from becoming an endangered species, the activity of squalene synthase has been well exploited. This chapter is focused on the engineering of isoprenoid biosynthetic pathway in W. somnifera by the introduction of squalene synthase gene to improve the yield of desired product.

Screening of osmotic stress-tolerant bacteria for plant growth promotion in wheat (Triticum aestivum L.) and brinjal (Solanum melongena L.) under drought conditions - Patel, P.; Patil, T.; Maiti, S.; Paul, D.; Amaresan, N. (Letters in Applied Microbiology, 2022)
Drought stress adversely affects plant growth and productivity. Therefore, the application of plant growth-promoting bacteria is a viable option for combating drought resistance in crops. In this study, 144 bacteria were isolated from the Kutch desert soil in Gujarat. Based on osmotic stress tolerance and PGP properties, two strains, Bacillus tequilensis (KS5B) and Pseudomonas stutzeri (KS5C) were tested for their effect on wheat (Triticum aestivum L.) and brinjal (Solanum melongena L.) under drought stress conditions. Inoculation with osmotic stress-tolerant bacteria showed 15 center dot 15-29 center dot 27% enhancement in root length of wheat and 15 center dot 27-32 center dot 59% in brinjal plants. Similarly, the enhancement of shoot length ranged from 14 center dot 72 to 37 center dot 70% for wheat and 59 center dot 39-95 center dot 94% for brinjal plants. Furthermore, the inoculated plants showed significant improvement in chlorophyll content and antioxidant properties such as proline, peroxidase and polyphenol oxidase activity compared to the control. Therefore, the bacterial strains identified in this study can be used to mitigate drought stress and enhance plant biomass.
Keywords: Antioxidant; brinjal; drought; plant growth; Wheat